2011
DOI: 10.1080/14786435.2010.523720
|View full text |Cite
|
Sign up to set email alerts
|

Response of fcc metals andL12andD022type trialuminides to uniaxial loading along [100] and [001]:ab initioDFT calculations

Abstract: Although the response of both pure fcc metals could be expected to be very similar, our results show a fundamental difference: whereas for Cu a special invariant state with C 22 = C 23 , leading to a bifurcation from the tetragonal to an orthorhombic deformation path, is reached at a strain of 10%, for Al this state is reached only at a strain of 33% close to the critical strain defining the ideal tensile strength. The reaction of the L1 2 -type trialuminides is comparable to the response of Al, no bifurcation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The shear deformations have been performed in an alias mode; 29,30,48 that is, the strain is applied to the top layer of the supercell, while the bottom layer is kept in a fixed position and all intermediate layers are free to relax. The alias regime provides a more realistic description of a shear deformation than an affine transformation applied to all coordinates in the cell.…”
Section: A {211} 111 Shear Deformationmentioning
confidence: 99%
See 1 more Smart Citation
“…The shear deformations have been performed in an alias mode; 29,30,48 that is, the strain is applied to the top layer of the supercell, while the bottom layer is kept in a fixed position and all intermediate layers are free to relax. The alias regime provides a more realistic description of a shear deformation than an affine transformation applied to all coordinates in the cell.…”
Section: A {211} 111 Shear Deformationmentioning
confidence: 99%
“…Again the energy-strain and stress-strain curves of NiAl and FeAl were found to be very different, leading to the conclusion that the instabilities under 111 shearing and 100 tension can be attributed to the same mechanism for FeAl, but not for NiAl. Jahnatek et al 29,30 have demonstrated that the chemical decoration of the fcc lattice in L1 2 and D0 22 -type trialuminides of Sc, Ti, and V determines similarities and differences in the response to 110 and 100 uniaxial loading compared to fcc Al.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is generally believed that the lower symmetry of D0 22 structure is the main cause of poor ductility. Many attempts had been made to convert D0 22 into L1 2 , which can make the aluminide have good ductility [12][13][14][15]. However, the D0 22 structure has a good strengthening effect in the recent design of high entropy alloy.…”
Section: Introductionmentioning
confidence: 99%